Biomaterials at the forefront: A comprehensive review of patented biomedical applications - Saik Safia Kousar, Rozette Hasse, Arnab Mukherjee, K. S. Mukunthan (Journal of Applied Pharmaceutical Science, 2024)
Over the years, biomaterials have played a crucial role in mitigating the socio-economic burden of healthcare by significantly enhancing the diagnosis and treatment of injuries and diseases. Through collaborative innovations, newly developed biomaterials have not only contributed to saving lives and alleviating suffering but have also improved the overall quality of life. The burgeoning biomaterials market witnessed considerable expansion over the past decade owing to escalating demands for medical implants, increased prevalence of diseases among the geriatric population, and a rise in cosmetic and plastic surgeries. This growth trajectory indicates substantial potential for further expansion in the forthcoming years. Consequently, there has been a surge in requests for research and development of novel biomaterials for biomedical applications from governmental entities, academic institutions, and private enterprises, leading to a significant rise in the number of biomaterial patents issued annually. This study presents a comprehensive review of the escalating interest in novel biomaterial patents within the biomedical domain over the last decade, which has promoted stupendous technological advancements in orthopaedics, dentistry, ophthalmology, and disease treatment. The promising outcomes of biomaterial-based research in the biomedical field pave the way for the emergence of smart biomaterials engineered through 3D and 4D printing technologies, capable of cell culturing, growth factor integration, and accurate emulation of complex body geometries. The future of biomaterials holds immense potential for transformative contributions to biomedical science and healthcare practice.
Keywords: Biomaterials, biomedical, orthopaedic, orthodontic, ophthalmic, diseases, 4D printing